Analysis of the Uses of Simple Planes in Everyday Life - Dwi Ratnawati; Erva Karimatunisa; Eka Budi Nur Prasetya; Wahyu Kurniawati (Educare: Journal Educational and Multimedia, 2024)
The aim of this research is to examine and analyze the role of simple airplane material in learning science at MI/SD level. The method used is qualitative with a descriptive approach. This research aims to analyze the use of simple aircraft in everyday life. A simple machine is a tool used to change the force exerted on an object into a larger or smaller force. The research obtained states that a simple machine consists of an arrangement of simple tools to help with daily activities which include levers, inclined planes, pulleys and wheels with axles. This research can help readers understand the importance of simple machines in everyday life and how to use them effectivelyn.